ECONOMIC CRISIS, DEGLOBALIZATION AND HUMAN RIGHTS: THE CHALLENGES OF THE COSMOPOLITAN CITIZENSHIP IN THE VIEW OF DISCOURSE THEORY - Bittar, Eduardo C.B. (PANORAMA OF BRAZILIAN LAW, 2015)
This article ‘Economic crisis, deglobalization and human rights discusses the challenges of the cosmopolitan citizenship in the perspective of discourse theory, reflecting on the devices and perspectives of human rights culture in the contemporary changing legal paradigms.